The Wedding of Infanta Juana and count of Brittan John IV (1386). Charles II Evreux diplomatic relations (Estudios de Historia de España, 2019)
Despite the unfavorable conditions imposed in the Castile Peace Treaty, King Charles II of Navarra, restless fighter, continues the narrow path of negotiations allowed by the clauses in the Treaty of Briones. The documentation kept in the General Archive of Navarre enables us to follow the various and arduous negotiations —initiated in 1384 and ended in 1386 in Pamplona— among the Navarre and Breton ambassadors up to the final agreement. By the middle of the year, the final clauses of the alliance of the wedding of Juana and Duke of Brittany John IV were signed. Duke John IV had been left a widower by two English princesses and, to that moment, had no heirs. Truly a triumph of the King of Navarra who attains the union and the consequential support of one of the most wayward vassals of the French kingdom.
Keywords: Wedding; Infanta; Diplomacy; Dowry; XIV Century